Study on the Effect of Oyster Mushroom Flour Addition on The Quality of Mackerel Tuna (Euthynnus affinis) Meatball - Nefitri, Allenty; Sari, N Ira; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was aimed to study the effect of oyster mushroom flour addition on mackerel meatball quality. The research design used was completely randomized design (CRD) non factorial which consisted of 4 treatments: without oyster mushroom flour (T0), 2% of oyster mushroom flour (T1), 4% gram oyster mushroom flour (T2) and 6% oyster mushroom flour (T3). The parameters used were sensory analyses, chemical analysis, and fiber content. The results showed that oyster mushroom flour addition to mackerel meatball processing affected on the appearance, texture, taste and chemical characteristic, however did not affect on the aroma and folding test value. The best treatment was addition of 4% oyster mushroom flour (T2), which was showing the sensory characteristic of intact and clean appearance with bright white cream color, the fish aroma was not strong, elastic and solid textured, and delicious fish tasted. The product contained 67.52% water, 2.91% ash, 16.08% protein, 2.59% fat and 3.0% fiber.Keywords: mackerel tuna fish, meatball, oyster mushroom flour